PENGARUH HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN BERAS ORGANIK DI JAKARTA - Abadi, Ferryal; Herwin, Herwin (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to analyze the effect of price, product quality and service quality on purchasing decisions for organic rice at the Indonesian Organic Community (KOI). This study has a type of quantitative research with respondents as many as 270 people who are customers of the Indonesian Organic Community (KOI). The research method will be conducted using primary data with structural equation modelling as a data processing model. This research is expected to produce a deep understanding of the factors that significantly influence the decision to buy other organic products and managerial proposals that are necessary for the development of the organic food business, especially rice.